ANALISIS PENGARUH LEVERAGE TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR PERDAGANGAN BESAR BARANG PRODUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - B11108003, Nur Aisyah (Jurnal Manajemen Update, 2013)
The aim of this research is to determine how is the relationship or the financial leverage effect towards the profitability in the sub-sector trade company that have registered in the production Stock Exchange. The population in this research is the companies in the sub-sector industry good product trade that have registered in the production registered Stock Exchange since 2006 to 2010. There are seven (7) companies that used as the sample have taken by using purpose sampling. The researcher used multiple linear regression as the analysis technique in this research. By using multiple linear regresion analysis that have done since 2006 to 2010, have found negative and significant effect between financial leverage and PER towards profitability, and there is a positive and significant effect between Size and Companys Value towards the company's profitability . The results of this research showed simultaneously the effect of leverage significantly (debt ratio), PER, Size and Companys Value towards profitability (ROA). Keywords: ROA, Debt Ratio, PER, Size and Companys Value, Wholesale Goods Production Subsector Registered in IDX